Safety of Fixed drug Combination in Post –Operative Cataract Patients, at Tertiary Care Centre – In South India - Vidyadevi, M; Anuradha, A; Rashmi, G; Shilpa, R; Nishath, S (Nepalese Journal of Ophthalmology, 2017)
Introduction: Cataract is any opacification in lens or its capsule, which accounts for about 50% of treatable blindness worldwide. The prevalence of cataract in India is about 62.6%. The incidence of post operative endophthalmitis ranges from 0.05% -0.14% and so the use of post-operative antibiotics and steroids is necessary to control infection and prevent inflammation. Fixed drug combinations not only cut the cost but also the dosage & improve the compliance of patients in the immediate post operative period. In this regard, the present study was conducted with the aim of studying the efficacy of using fixed drug combination (Difluprednate and Moxifloxacin) in reducing ocular inflammation & pain in post-operative patients undergoing cataract surgery. Methodology: Study design: Prospective interventional study, in which 749 eyes underwent SICS with IOL. All of them were treated with Difluprednate and Moxifloxacin, combination eye drops postoperatively 4 times a day, and reviewed on day 1, 5 and once in two weeks up to 6 weeks. Results: Out of 749 eyes, 730 were normal, 10 eyes had minimal raise in IOP in the range of 21 mmHg-31mmHg (considering 21mmHg as baseline) which decreased without any intervention within 3 weeks and only 9 eyes had raise in IOP of more than 31mmHg, which did not decrease in spite of discontinuing the drops and needed anti-glaucoma treatment. Conclusion: Our study clearly shows that fixed drug combination of antibiotic and steroid does not cause raised IOP in about 97% of cases of SICS in the post-operative period and also improves the compliance of the patients.